Religiosity-Based Social Development And Programmatic Politics At The Local Level - Sri Sutjiatmi; Diryo Suparto; Hartuti Purnaweni; Agus Setio Widodo; Erny Rosyanti (Pusat Publikasi Nusantara, 2023)
This study discusses social development based on religiosity and programmatic politics. Both are discussed in depth in this research so that readers can find descriptions and analysis points from various points of view. The urgency in this research is to find out that social development must be accompanied by innovation, citizen participation and the central role of the creator, namely the Tanjung Village Government. The construction of the Islamic Center in the village of Tanjung is a trigger for increasing religiosity, ease of access to educational facilities and in the long term will give birth to social piety and improve the quality of human resources in the surrounding community. The results of the research show that social development innovations involving external partners will produce optimal results but with the condition that there is active participation of its citizens. Good development starts from the aspirations of the residents and has been programmed, therefore the Head of the Tanjung Er Suwardi village is trying to make it happen, a good image as the figure behind the success of development will stick with him so that he will be able to be re-elected in the next Pilkades. This research has deficiencies that can be refined through further research by focusing more on the negative impacts of social development in order to further enrich the reader's knowledge that social development can also have undesirable impacts.